2014
DOI: 10.1080/15257770.2014.880479
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Adenine Nucleotide Catabolism in Heart Valves

Abstract: Enzymes of extracellular nucleotide catabolism, such as ecto-nucleoside triphosphate diphosphohydrolase (eNTPD), ecto-5'-nucleotidase (e5NT) and ecto-adenosine deaminase (eADA), control extracellular concentrations of adenine nucleotides and adenosine, furthermore in that way regulate inflammation, immune response, and platelets aggregation. In valves, disturbances of these processes may lead to their dysfunction and calcification. The aim of this study was to analyze the distribution of enzymes, which are eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…First we found CD73 activity among the highest in the human body [10,46]. Furthermore, we found that human valve interstitial cells could be shifted toward osteoblast phenotype with high alkaline phosphatase activity by exposure to ATP or non-hydrolizable ATP analog while exposure to adenosine block this transformation [47].…”
Section: Cd73 and Arterial Calcificationsmentioning
confidence: 93%
See 1 more Smart Citation
“…First we found CD73 activity among the highest in the human body [10,46]. Furthermore, we found that human valve interstitial cells could be shifted toward osteoblast phenotype with high alkaline phosphatase activity by exposure to ATP or non-hydrolizable ATP analog while exposure to adenosine block this transformation [47].…”
Section: Cd73 and Arterial Calcificationsmentioning
confidence: 93%
“…The presence of this enzyme is also confirmed on leukocytes derived from peripheral blood, thymus, spleen and lymph node. Such widespread organ distribution is related to its high abundance in endothelium [9,10]. Ecto-5 0 -nucleotidase is also expressed by a considerable variety of tumor cells [11].…”
Section: Cd73: Cellular Function and Structurementioning
confidence: 99%
“…7A). There was a significant (p<0.05) down-regulation of transcripts involved in adenine nucleotide synthesis and conversion, such as Entpd2 (Ectonucleoside triphosphate diphosphohydrolase 2) and Nme3 (Nucleoside diphosphate kinase 3) [30,31], but only in the HdhQ150 mouse model (p<0.05) (Fig. 7B).…”
Section: Transcriptional Remodeling Of Genes Involved In the Synthesimentioning
confidence: 99%
“…Nucleotides may also be catabolized by other enzymes such as ecto-nucleotide pyrophosphatases/ phosphodiesterases (eNPPs) or alkaline phosphatase (ALP) [22,23]. Upstream pathways, which lead to extracellular ATP synthesis from AMP are the least important, because of the minimal ecto-kinase activity [24]. Except for the removal of nucleotides from the extracellular space, the significant function of ecto-nucleotidases is the production of adenosine, which attenuates inflammation and platelets reactivity [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%